Rafael Lapesa: De Ayala a Ayala. Madrid, Istmo, 1988. Colección Bella Bellatrix. 359 p. 22,5 x 14,5 cm. - Zuleta, Emilia de (1989)
Fil: Zuleta, Emilia de. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras